Unravelling the tumour- and cancer stem cell (CSC)-regulatory roles of miR-3934-5p in human breast cancer - Chong, Zhi Xiong (2024)
MicroRNA (miRNA) is a small non-coding RNA. It can interact with the untranslated region of messenger RNA (mRNA) to suppress protein translation. It can also attach to gene promoters to enhance gene transcription. The published work from our group previously showed that cisplatin resistant cancer stem cells (CSCs) isolated from a triple-negative breast cancer (TNBC) cell line (MDA-MB-231) displayed significant upregulation of exosomal miR-3934-5p. However, the underlying mechanism that explains this cellular phenomenon is unclear. Besides, it would also be intriguing to evaluate whether miR-3934-5p affects the development of other breast cancers, like luminal A (ER- and PR-positive) breast cancer (MCF-7). To narrow this gap in the literature, this study aimed to evaluate the cancer- and CSC-controlling role of miR-3934-5p in MDA-MB-231 and MCF-7 using an in vitro functional study approach.